PENGARUH PROFESIONALISME AUDITOR, GAYA KEPEMIMPINAN DAN KEPUASAN KERJA SEBAGAI PEMODERASI TERHADAP KUALITAS KINERJA AUDITOR PADA KAP MALANG - Siti Masruroh; Nur Hidayati; Afifudin Afifudin (Universitas Islam Malang, 2019)
ABSTRACTThe quality of the audit is the result of the auditor's performance in fulfilling the tasks to be performed Concerned. Accountants need to be able to provide a high quality audit in order to have a high degree of accountability to the parties involved in the financial statements. The aim of this study is to analyze the influence of professionalism, management style and job satisfaction on the quality of the examiner's performance. The population in this study are accountants who work at the Chartered Accountancy in Malang with at least one year of professional experience. Sampling takes place using a dedicated sampling method and the number of samples is 58. This research is a form of explanatory research, and this research model is quantitatively descriptive, namely data related to numbers that still need to be processed and analyzed for research purposes. The method of data collection is done by distributing questionnaires directly to the examiner who works for the accounting firm in the city of Malang. The data analysis technique used in this studyis a multiple regression analysis technique. The results of the hypothesis test show that professionalism, leadership style and job satisfaction both have a positive and significant impact on the quality of the audit.Keywords: auditor, professionalism, management style, job satisfaction, explanation, questionnaire